OPDA Has Key Role in Regulating Plant Susceptibility to the Root-Knot Nematode Meloidogyne hapla in Arabidopsis - Gleason, Cynthia; Leelarasamee, Natthanon; Meldau, Dorothea; Feussner, Ivo (Frontiers in Plant Science, 2016)
Jasmonic acid (JA) is a plant hormone that plays important roles in regulating plant defenses against necrotrophic pathogens and herbivorous insects, but the role of JA in mediating the plant responses to root-knot nematodes has been unclear. Here we show that an application of either methyl jasmonate (MeJA) or the JA-mimic coronatine (COR) on Arabidopsis significantly reduced the number of galls caused by the root-knot nematode Meloidogyne hapla. Interestingly, the MeJA-induced resistance was independent of the JA-receptor COI1 (CORONATINE INSENSITIVE 1). The MeJA-treated plants accumulated the JA precursor cis-(+)-12-oxo-phytodienoic acid (OPDA) in addition to JA/JA-Isoleucine, indicating a positive feedback loop in JA biosynthesis. Using mutants in the JA-biosynthetic pathway, we found that plants deficient in the biosynthesis of JA and OPDA were hyper-susceptible to M. hapla. However, the opr3 mutant, which cannot convert OPDA to JA, exhibited wild-type levels of nematode galling. In addition, mutants in the JA-biosynthesis and perception which lie downstream of opr3 also displayed wild-type levels of galling. The data puts OPR3 (OPDA reductase 3) as the branch point between hyper-susceptibility and wild-type like levels of disease. Overall, the data suggests that the JA precursor, OPDA, plays a role in regulating plant defense against nematodes.